Facilitating desistance from aggression and crime: theory, research, and strength-based practices - Langton, Calvin M.; Worling, James R. (John Wiley & Sons, Inc, 2022)
Desistance theory and forensic practice / Andrew Day & Mark Halsey -- Contributions to desistance research from developmental psychopathology / Keith Burt, Virginia Peisch & Elyse Rosenberg -- Contributions to desistance research and practice from positive psychology / Yilma Woldgabreal & Andrew Day -- Risk and strength variables in recidivism-desistance prediction research with applied assessment practices : toward a nomenclature for their effects / Calvin M. Langton, Gabriela D.B. Sheinin & James R. Worling -- Questions about strengths in treatment work in forensic practice / Calvin M. Langton, Daniel Pillersdorf, Meredith J. Awrey & James R. Worling -- Strengths in the risk-needs-responsivity model of offender assessment and rehabilitation / J. Stephen Wormith & Kayla E. Truswell -- Desistance from conduct problems during childhood : potential explanatory factors and assessment / Anna-Karin Andershed & Henrik Andershed -- Assessment of protective factors in youth justice settings / Chi Meng Chu, Xuexin Xu, & Dongdong Li -- Factors related to desistance from sexual recidivism / James R. Worling, Toronto, Canada, & Calvin M. Langton -- Women's desistance from crime : the role of individual, relational and socio-structural factors over time / Anne-Marie Slotboom, Elanie Rodermond, & Jan Hendriks -- Factors predicting desistance from intimate partner violence perpetration in adults / Patti A. Timmons Fritz & Jewels Adair -- Factors predicting desistance from criminal and aggressive behavior in mentally disordered individuals / Michiel de Vries Robbé -- Factors predicting desistance from criminal behavior and aggression in adult offenders : a critical review / Kirk Heilbrun, David DeMatteo, Rebecca Schiedel, Victoria Pietruszka, Jaymes Fairfax-Columbo, & Shelby Arnold -- Evidence-based delinquency prevention for children exhibiting conduct problems / Dustin A. Pardini & David A. Hawes -- Strengths-based approaches to address criminal behaviors in adolescents / Alan Carr, Dan Hartnett, & Jane Meleady -- Strength-based treatments for adults and juveniles who have been sexually abusive : Aareview / W. L. Marshall, & L.E. Marshall -- Strengths-based approaches to the treatment of incarcerated women and girls / Gina Fedock & Stephanie S. Covington -- Strengths-based batter intervention programs for intimate partner violence / Kristin W. Bolton, Jon C. Hall, Peter Lehmann, Mercedes Wilkins, Catheleen Jordan -- Strength-based approaches with offenders with mental illness / Tonia L. Nicholls, Karen Petersen, Lindsey Kendrick-Koch, Barinder Singh, Hayley Ross, & Christopher Webster -- The good lives model : next steps in research and practice / Sophie R. Dickson & Gwenda M. Willis.